Adaptive Damping of a Double-Beam Structure Based on Magnetorheological Elastomer - Tomasz Szmidt; Dominik Pisarski; Robert Konowrocki; Stefan Awietjan; Anna Boczkowska (Shock and Vibration)
A method of vibration reduction based on activation of an MRE block that couples twin cantilever beams at their free ends is investigated. Four types of magnetorheological elastomers have been manufactured, and their rheological properties in a range of magnetic field intensities are established. Free vibrations of several double-beam structures with controllable damping members made of these MREs are investigated, and a method of semiactive control of such structures is proposed. The effects of compression of the elastomers and alignment of the magnets used to activate them are reported. The mathematical modeling of the system is verified experimentally.